INVOKE‐2: A phase 2 randomized, double‐blind, placebo‐controlled study to evaluate the efficacy and safety of AL002 in participants with early Alzheimer's disease. (31st December 2021) - Paul, Robert; Jackson, Sam; Ward, Michael; Joshi, Aashka; Castro, Abraham; Yeh, Felix L; Liao, Yijie; Morrison, Glenn
Abstract: Background: Triggering receptor expressed on myeloid cells 2 (TREM2) is expressed in the brain predominantly by microglia. Mutations in TREM2 cause an increased risk of developing Alzheimer's Disease (AD). E.g., the R47H coding variant confers similar risk for AD as does one copy of APOE4. AL002 is a humanized monoclonal IgG1 antibody (mAb) that activates the TREM2 signaling pathway to increase the ability of microglia to clear pathology and protect neurons. AL002 is believed to be the first anti‐TREM2 mAb in clinical development for the treatment of AD. AL002 was generally well tolerated in a Phase 1 study (INVOKE) and has demonstrated proof of target engagement and proof of mechanism. These results have supported progressing AL002 to the INVOKE‐2 Phase 2 study of AL002 in patients with early AD. Method: INVOKE‐2 is a randomized, double‐blind, dose‐ranging, placebo‐controlled study to evaluate the efficacy and safety of AL002 in participants with early AD (NCT04592874). This is a global study that will enroll approximately 265 participants in North America, Australia, New Zealand, Europe, and South America. Participants will be randomized to receive one of 3 doses of AL002 or placebo, administered via IV infusion every 4 weeks, for up to 96 weeks. The objectives of this Phase 2 study are to assess the efficacy and safety of AL002. Result: All participants must have a diagnosis of early AD with evidence of cerebral amyloidosis and a clinical severity consistent with Stage 2 to early Stage 4 (2018 Research Framework), including a CDR‐GS of 0.5 or 1, MMSE from 22 to 30, and RBANS DMI of 85 or lower. Efficacy will be assessed with clinical outcome assessments (including CDR‐SB and ADAS‐Cog13), and fluid and imaging biomarkers. Safety will be assessed through monitoring of AEs, suicidality assessments, changes in laboratory and vital signs, ECG and MRI. PK in serum and CSF will be assessed. Conclusion: INVOKE‐2 is designed to investigate the efficacy and safety of AL002, representing a novel, first‐in‐class neuro‐immunological approach for treating AD. Enrollment is ongoing.